Prevalence and correlates of cigarette smoking among Dulong adults in China: A cross-sectional survey in 2020 - Shao, Ying; Zha, Shun; Qin, Mingfang; Zhu, Qiuyan; Yang, Xiliang; Yang, Cangjiang; Wang, Xinlin; Zhang, Yanli; Yang, Weimei; Zhou, Kunhua; Li, Yanmei; Tang, Xian; et al. (Frontiers in Public Health, 2022)
Background: The Dulong people isare one of the minorities in China with the lowest population in China. In recent years, the lifestyle of the Dulong people haves also changed drastically due to income growth and urbanization. This study aims to identify the prevalence and potential factors related to cigarette smoking prevalence and potential risk factors among Dulong adults in China. Method: This study was part of conducted among 1,018 adults based on the Dulong Health Status Investigation and Evaluation (DHSIE) in Gongshan Dulong and Nu Autonomous County of Yunnan province, Southwest China (n=1018). A cross-sectional design and face-to-face questionnaire were used to collect cigarette smoking habits and demographic information. Data were weighted by post-stratification weights according to the age and gender composition of Dulong resident. We also analyzed univariate and multivariate unconditional logistic regression to explore current smoking correlates. Results: The weighted prevalence of ever-smoking, currently smoking, and formerly smoking among Dulong adults are 31.3%, 27.7%, and 3.6%, respectively. The prevalence of ever-smoking and currently smoking of among males (57.0% and 50.6%) is much higher than that of females (4.0% and 3.4%). Nearly 60% of ever-smokers and current smokers smoked more than 20 cigarettes per day, which are higher than former smokers (35.2%). Among current smokers, 33.1% were relapsed smokers, and 28.3% intend to quit smoking. By adjusting for potential confounding variables, multiple logistic regression analysis indicated that participants who are male participants (OR = 48.982, 95% CI: 25.026-95.869) and current drinkers (OR = 4.450, 95% CI: 2.556-7.746) are more likely to be current smokers. On the other hand, cCurrent smokers are also more likely to be exposed to second-hand smoke (OR = 4.269, 95% CI: 2.330-7.820) and have a higher risk of chronic respiratory disease (OR = 4.955, 95% CI: 1.669-14.706). Conclusions: Cigarette smoking is highly prevalent among the Dulong people in Southwest China. An aAppropriate and effective tobacco control strategy is an urgent need for this population.